Answer:
C
Step-by-step explanation:
Answer:
6
Step-by-step explanation:
- 6x +5 = 0
- 6x + 9 -9 +5 = 0
[ - 6x + 9] - 4 =0
-4 = 0
= 4
(x-3) = or (x-3) = -
(x-3) = 2 or (x-3) = -2
x = 5 or x = 1
therefore, sum of these solutions is 5+1 = 6
F(x) = 6x + 5
g(x) = 6x - 5
f(g(x)) = 6(6x - 5) + 5 = 36x - 30 + 5 = 36x - 25
g(f(x)) = 6(6x+ 5) - 5 = 36x + 30 - 5 = 36x + 25
f and g are not inverse of each other.
Answer:
<u></u>
- <u>a) P(X=1) = 0.302526</u>
- <u>b) P(X=5) = 0.010206</u>
- <u>c) P(X=3) = 0.18522</u>
- <u>d) P(X≤3) = 0.92953</u>
- <u>e) P(X≥5) = 0.010935</u>
- <u>f) P(X≤4) = 0.989065</u>
Explanation:
Binomial experiments are modeled by the formula:
Where
- P(X=x) is the probability of exactly x successes
- p is the probability of one success, which must be the same for every trial, and every trial must be independent of other trial.
- n is the number of trials
- 1 - p is the probability of fail
- there are only two possible outcomes for each trial: success or fail.
<u>a.) P (x=1)</u>
<u></u>
<u>b.) P (x=5)</u>
<u>c.) P (x=3)</u>
Using the same formula:
<u>d.) P (x less than or equal to 3)</u>
- P(X≤3)= P(X=3) + P(X=2) + P(X=1) + P(X=0)
Also,
- P(X≤3) = 1 - P(X≥4) = 1 - P(X=4) - P(X=5) - P(X=6)
You can use either of those approaches. The result is the same.
Using the second one:
- P(X=4) = 0.059335
- P(X=5) = 0.010206
- P(X=6) = 0.000729
- P(X≤3) = 1 - 0.05935 - 0.010206 - 0.000729 = 0.92953
<u>e.) P(x greather than or equal to 5)</u>
- P(X≥5) = 0.010206 + 0.000729 = 0.010935
<u>f.) P(x less than or equal 4)</u>
- P(X≤4) = 1 - P(X≥5) = 1 - P(X=5) - P(X=6)
- P(X≤4) = 1 - 0.010206 - 0.000729 = 0.989065